Freedom writers [videorecording (DVD)] - LaGravenese, Richard; LaGravenese, Richard; Swank, Hilary; Dempsey, Patrick, 1966-; Glenn, Scott, 1942-; Gruwell, Erin (Paramount, 2017)
A young teacher takes on a class of at-risk students in a violent high school, inspiring them to learn tolerance and to apply themselves through daily writing in a journal.